Biological synthesis and characterization of lead oxide nanoparticles using Averrhoa bilimbi Linn. aqueous extract - Thanawat Sutjaritvorakul; Sutee Chutipaijit (My University, 2020)
Lead oxide (PbO) is an important semiconductor material, and it can be potentially applied in many industries such as glass, battery and electronic industry. Metal nanoparticles are commonly synthesized by chemical and physical methods. However, these methods require extreme conditions, and thus causing toxic compounds. To overcome these problems, biological method for synthesis has been developed because it is more environmentally-friendly process. The objective of this research was to synthesize and characterize PbO nanoparticles (PbO-NPs) using aqueous fruit extract of Averrhoa bilimbi Linn. The metal nanoparticles were investigated for the morphological characteristics and chemical composition by scanning electron microscope (SEM) equipped with energy dispersive X-ray spectroscopy (EDS), and were identified by X-ray powder diffraction (XRD) and Fourier transform infrared (FTIR). The XRD pattern and FTIR spectrum substantiated that the metal nanoparticles were lead oxide. It was found that the aqueous fruit extract of A. bilimbi can synthesized PbO-NPs. Therefore, this method can be a promising alternative for low cost and non-polluting production of PbO-NPs.
Keywords: Lead oxide; Nanomaterials; Characterization; Energy-dispersive X-ray spectroscopy; Nanoparticles: synthesis and applications